State of Play for 100% Renewable Energy Futures for Cuba: Recent Changes and Challenges - Korkeakoski Mika (MDPI, 2022)
Over the last decades Cuba has been remarkably successful at revitalizing its energy sector by significantly increasing efficiency and reducing energy intensity and emissions. These achievements, made through a comprehensive approach targeting infrastructure, consumption habits and people's understanding of energy issues, can provide Cuba with fertile ground on which to tackle the policy challenges ahead in order to achieve its 2030 energy policy goals. This review carries out a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis of the late 2010s until 2022 on the variety of changes that have taken place and the challenges still ahead. Overcoming critical challenges under the Political, Economic, Social, Technological, Environmental and Cultural (PESTEC) conditions is crucially important; how will Cuba be able to tackle the challenge of implementing the transition to renewable energy and find the resources to actualize the 2030 vision?